Exploring the Role of Personalization in Adaptive Learning Environments - Graf, Alex (International Journal Software Engineering and Computer Science (IJSECS), 2023)
: In recent years, the integration of technology in education has sparked interest in enhancing learning experiences. Adaptive learning environments, which customize educational content and strategies to individual learners, offer a promising approach. Personalization within adaptive learning environments is crucial for addressing learner diversity and maximizing engagement and learning outcomes. This research project aims to explore the role of personalization in adaptive learning environments and its impact on the user experience and educational outcomes. By investigating the effectiveness of personalized interfaces and adaptive strategies, we seek to understand how these technologies can create more engaging and effective learning environments. The project objectives are threefold. Firstly, we aim to design and implement adaptive learning interfaces with personalized elements to customize the learning experience for each user. Secondly, we will evaluate the impact of personalization on user experience dimensions, including engagement, satisfaction, and motivation. Lastly, we will assess the effect of personalization on learning outcomes, such as knowledge acquisition and retention. This research contributes to the field of educational technology and user experience (UX) design. By examining the role of personalization in adaptive learning environments, we aim to inform the development of more effective and learner-centered educational tools and strategies.